The common component of CPI: An alternative measure of underlying inflation for Canada - Mikael Khan; Louis Morel; Patrick Sabourin (Bank of Canada, 2013)
In this paper, the authors propose a measure of underlying inflation for Canada obtained from estimating a monthly factor model on individual components of the CPI. This measure, labelled the common component of CPI, has intuitive appeal and a number of interesting features. In particular, it is not affected by sector-specific price movements that can distort the signal in many other measures of underlying inflation, and appears to capture price movements that are indicative of aggregate demand fluctuations in the Canadian economy. This indicator may serve as a useful complement to existing measures of underlying inflation monitored by the Bank of Canada.
Keywords: C1; E31; E32; E52; E58; 330; Econometric and statistical methods; Inflation and prices; Business fluctuations and cycles; Monetary policy framework